Computing field losses for furrow irrigation - Benham, Brian, author (Colorado State University. Libraries, 1998)
The goal of every irrigator should be to apply the right amount of water as uniformly as possible to meet the crop needs. To do the job right, irrigators need to take into account how much water is applied during irrigation and where the water goes (uniformity). Achieving a uniform water application is not easy when using furrow irrigation. However, with a better understanding of how irrigation system management affects water distribution and a willingness to make management changes, the uniformity and efficiency of most systems can be improved. This paper outlines the use of the "cutoff ratio" and how irrigators can use this management parameter to evaluate irrigation system performance.
Not digitized by CSUL Digital Services.
Presented at the Central Plains irrigation short course and exposition on February 17-18, 1998 at the Camino Inn in North Platte, Nebraska.